Comparative evaluation of Bethesda system with conventional reporting method in assessment of thyroid malignancy rate - Dr. Manglesh Kumar Srivastava; Dr. Kanchan Srivastava; Dr. M.Q. Baig; Dr. Asharam; Dr. Shilpa Vahikar (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Fine needle aspiration cytology (FNAC) of thyroid is non-invasive, cost-effective & extremely useful technique in identifying a substantial proportion of thyroid nodules as benign & appropriately triages patients with thyroid cancer to appropriate surgery. The Bethesda system for reporting thyroid cytology represents a major step towards improved clinical significance, reproducibility, standardization & greater predictive value of FNAC thyroid.Objective: To categories thyroid lesions according to Bethesda system & to determine the rate of malignancy in each cytologic category by correlating the result with histopathologic diagnosis on the resected specimens.Material & Methods: The present study was carried out on 100 patients of thyroid swelling referred to the department of pathology, for FNAC. The reporting was done by using Bethesda system of thyroid cytopathology in comparison to the conventional reporting system. The malignancy rate based on final histopathologic evaluation was analyzed for each of the cytologic groups.Results: Rates of malignancy in each category of conventional system reported on follow up HPE were 16.66% in non-diagnostic group, 2.17% in colloid garter, nil in colloid cyst, 25% in thyroiditis, 7.69% in follicular lesion/ neoplasm, 33.33% in indeterminate group, 75% in suspicious for malignancy & 100% in malignant category. Rates of malignancy in each category of Bethesda system on follow up HPE were 16.66% in Non Diagnostic, 1.58% in benign category, 28.57% in atypical of undermined significance, 18.18% in suspicious for follicular neoplasm, 80% in suspicious for malignancy & 100% in malignant category.Conclusion: By adapting the Bethesda cyto-pathology reporting system malignancy risk in the categories of AFLUS, SM & Malignant category help to determine a better patient outcome due to proper clinical management.